Формування ранньослов'янських поселенських структур за матеріалами досліджень пам'яток другої половини І тис. басейну р. Горині - Прищепа, Б.А. (Археологія і давня історія України, 2019)
У статті зібрано і проаналізовано інформацію про взаємне розміщення поселень празько-корчацької і райковецької культур в басейні р. Горині. Виділено окремі територіальні групи поселень, відомі в науковій літературі як гнізда поселень. Розглянуто їх внутрішню структуру, простежено динаміку розвитку від VI—VII ст. до Х ст., проведено порівняння із гніздами поселень, дослідженими на сусідніх територіях. The processes of Slavic settlement between the Dnipro and the Carpathians in the early Middle Ages have been studied unevenly. Scientists characterized them based on the materials from Eastern Volhynia, Northern Bukovina, and Eastern Podillia. New archaeological sources obtained during the research of the monuments of the second half of the first millennium in the basin of the Horyn River allow us to trace the dynamics of the settlement of ancient Slavs in certain micro-regions and the formation of early medieval settlement structures, and the influence of various factors on these processes. In its flow, the river passes different landscapes and physical and geographical zones in terms, and such natural diversity had a corresponding effect on the processes of settlement. In total, about 300 settlements of the early Slavs have been explored in the region. The comparison of data from different chronological stages indicates a significant increase in their number, from 38 in the 6—7th centuries to 262 in the 10th century, that is, in 6.9 times. The peculiarity of the placement of early Slavic settlements in the Horyn River basin was their concentration within the Volhynian Upland (over 85 % of all settlements of the Raikovets culture are located here) and the weak population of Volhynian Polissia. Beginning from the 6—7th centuries the formation of individual nests of settlements can be observed in Volhynian Upland. In the basins of small rivers and streams, the nests of settlements are easier to outline, because they, as a rule, have distinct natural boundaries on the watersheds. According to the materials of the Raikovets culture, the nests of settlements are better detected at the final stage of its development in the late 9—10th centuries. At this time, they can be distinguished not only by the concentration of unfortified settlements, but also by the fortifications and burial mounds. The archaeological sources of the 8—10th centuries allow to allocate the nests of settlements in the whole territory of the Volhynian Upland and along the Horyn River within Volhynian Polissia. Their area is determined by the size of the basins of small rivers and streams from 25 to 60 square kilometers. Gradually, the number of settlements in individual nests increased; in the 10th century, on the Volhynian Upland they counted from 4 to 11. The structure of such nests became more complicated, fortifications appeared, and burial mounds were formed. Territorial groups of the settlements of the same age, along with their resource base in the form of agricultural lands, pastures, forests, etc., according to the researchers, are the archaeological equivalent of the Slavic community.